Two New Species of Yponomeutoid Moths (Lepidoptera, Yponomeutidae, Plutellidae) from Madagascar - Gershenson, Z.S. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Описаны два новых вида молей: Rhabdocosma dolini Gershenson, sp. n. (Plutellidae) и Yponomeuta madagascariensis Gershenson, sp. n. (Yponomeutidae). Оба рода, к которым принадлежат эти виды, отмечены впервые для фауны Мадагаскара. Rhabdocosma dolini Gershenson, sp. n. (Plutellidae) and Yponomeuta madagas-cariensis Gershenson, sp. n. (Yponomeutidae) are described. Both genera of these species are recorded from Madagascar for the first time.